Breaking Down Barriers : Unlocking Africa's Potential through Vigorous Competition Policy - World Bank Group (World Bank, Nairobi, Kenya, 2016)
This report shows how competition policy can help African countries boost inclusive and sustainable development. Prepared by the World Bank Group (WBG) in partnership with the African Competition Forum, the study reviews the implementation of competition frameworks in Africa and examines competition issues that affect market performance in three important sectors for Africa's competitiveness: cement, fertilizers, and telecoms. It uses the WBG's Markets and Competition Policy Assessment Tool to identify how competition rule and their enforcement could be made more effective, and to highlight economic and regulatory characteristics of cement, fertilizers and telecoms markets that dampen competition and increase the risk of anticompetitive business practices. Conservative estimates put forward by this report suggest that addressing weak competition in principle staple foods across three countries would have the effect of lifting around 500,000 people above the poverty line by lowering consumer prices. Fundamental market reforms to increase competition in key input services would also boost economic growth. For example, professional services reforms would deliver an additional 0.16–0.43 percent of additional annual gross domestic product growth. While the benefits of competition are clearly observable in Africa, considerable effort is still required to ensure effective implementation of competition laws and incorporation of competition principles in government policies.